The Ethical Matrix as a Tool for Decision-Making Process in Conservation - Biasetti, Pierfrancesco; de Mori, Barbara (Frontiers in Environmental Science, 2021)
Decision making-process in conservation can be very complex, having to deal with various value dimensions and potential conflicts. In fact, conflicts and competing interests between stakeholders are among the most quoted reasons for failure of projects. Ethical analysis can be helpful in this regard. In this paper we present a revision of the Ethical Matrix specifically tailored to decision-making processes in conservation. The Ethical Matrix is a conceptual tool devised to help decision-makers by supplying them with a framework of the ethically relevant aspects involved in decision-making process. It was originally developed for the ethical assessment of agri-food biotechnologies and later has been applied to other fields. The revised version we propose here has been designed for the ethical analysis of conservation priority-setting and impact. As conservation can raise many ethical relevant controversies, conceptual tools like the one presented here can be of help for conservationists, providing a map of the value demands involved. This map can be used to question the reasonableness of the value judgments, estimate the impact of different courses of actions, anticipate conflicts, and rank their severeness.